(untitled) (Journal of the College of Basic Education, 2024)
Due to climate change represented by rising temperatures, And the lack of rainfall due to repeated drought cycles and the decrease in water supplies entering Iraq, As well as following primitive agricultural methods and unconscious use of natural resources, including water resources , Therefore, this research came to reveal the deterioration of soil and its increase in salinization in the center of Dhi Qar Governorate between the years (1993-2023). Using satellite data by employing spectral indicators and the outputs of the extensive analytical capabilities of Geographic Information Systems (GIS), Therefore, two satellite images were chosen for the Land sat satellite, one for the year 1993 and the second for the year 2023, Through these two visualizations, the high level of soil salinity in the study area was tracked and identified. The important indicators used to study the soil salinity index, represented by the salinity standard index (SI), And the modified soil salinity index (NDSI), The results of the indicators revealed a clear increase in the rates of soil salinization in the center of Dhi Qar governorate and an increase in the rate of change, especially in the type of lands with very high salinity. The results of the Salinity Standard Index (SI) revealed a high rate of change during the study period in the aforementioned variety, amounting to 183.25). As for the Modified Soil Salinity Index (NDSI), it also recorded a clear increase in the percentage change in the type of land with very high salinity, Amounting to (3514.45). It can be said that collecting the results of soil salinization indicators warns of soil deterioration in the study area during the last three decades. In order to preserve the soil and protect it from deterioration, It is necessary to adopt tools and methodologies that will stop soil deterioration and salinization in order to preserve this important natural resource.